Protecting urban wildlife fauna, fighting zoonoses, and preventing biophobia in Brazil - Kmetiuk, Louise Bach; Pettan-Brewer, Christina; Morikawa, Vivien Midori; Negrini, Vanessa; Chiba de Castro, Wagner Antonio; Maiorka, Paulo; Biondo, Alexander Welker (Frontiers in Conservation Science, 2025)
Biophobia has increased worldwide, particularly in high-income countries, leading to the loss of natural interactions and fewer health and wellbeing benefits for humans and animals. Wildlife avoidance in Brazilian urban settings has been mostly directed to synanthropic species (so-called “harmful fauna”) due to the risk of zoonosis and mostly involves bats, capybaras, opossums, and monkeys. Additionally, feral cats and stray dogs prey on vulnerable wildlife fauna, decreasing biodiversity. Wildlife protection groups have contributed to this biophobia by demanding the capture and relocation of local wildlife to distant states and federal parks. Nonetheless, some Brazilian state capitals peacefully coexist with steady or growing urban wildlife. Accordingly, this study aimed to present initiatives for wildlife protection, zoonosis surveillance, and biophobia prevention in Curitiba, the eighth-largest Brazilian city in the world and considered among the most sustainable cities in Latin America. Instead of sole sustainability, the One Health approach has been applied to address animal, human, and environmental health as part of city priorities, including free-of-charge veterinary services, basic school education, and a newly established public veterinary hospital. Animal Protection Services, City Secretary of Environment, has promoted substantial improvements in pet guardianship and urban wildlife fauna protection, with an updated city wildlife inventory, attendance, and release of native fauna into city parks. Meanwhile, the Zoonoses Surveillance Unit (ZSU), City Secretary of Public Health, has worked daily to prevent zoonoses and other public health issues, particularly bat rabies, with minimal impact on city wildlife. Children’s outreach and educational handbooks, inserted into teaching content in basic schools, are used to prevent biophobia in future generations. In summary, Curitiba may serve as a model for the One Health approach (in addition to sustainability) for the concomitant improvement of animal health and wildlife protection in major cities in Brazil and worldwide.